RedeAmericas: building research capacity in young leaders for sustainable growth in community mental health services in Latin America. (14th February 2017) - Yang, L.; Pratt, C.; Valencia, E.; Conover, S.; Fernández, R.; Burrone, M. S.; Cavalcanti, M. T.; Lovisi, G.; Rojas, G.; Alvarado, R.; Galea, S.; Price, L. N.; et al.
Abstract : The purpose of this paper is to describe the development and initial accomplishments of a training program of young leaders in community mental health research as part of a Latin American initiative known as RedeAmericas. RedeAmericas was one of five regional 'Hubs' funded by the National Institute of Mental Health (NIMH) to improve community mental health care and build mental health research capacity in low- and middle-income countries. It included investigators in six Latin American cities – Santiago, Chile; Medellín, Colombia; Rio de Janeiro, Brazil; and Córdoba, Neuquén, and Buenos Aires in Argentina – working together with a team affiliated with the Global Mental Health program at Columbia University in New York City. One component of RedeAmericas was a capacity-building effort that included an Awardee program for early career researchers in the mental health field. We review the aims of this component, how it developed, and what was learned that would be useful for future capacity-building efforts, and also comment on future prospects for maintaining this type of effort.